Pengolahan Limbah Cair Industri Tahu Menggunakan Metode Aerasi dan Koagulasi dengan Biji Kelor (Moringa Oleifera) - Ambia, Warisul; Dewi, Ratni; Rahmawati, Cut Aja (Jurnal Teknologi, 2024)
Tofu industrial waste is waste that contains high organic compounds, has the potential to damage the environment and needs to be followed up. This study used aeration and coagulation methods with moringa oleifera seed powder. The purpose of this study was to study the best time and mass of moringa seeds in removing COD (Chemical Oxygen Demand), TDS (Total Dissolved Solid) contaminants, conductivity, turbidity and pH of tofu industrial wastewater. This research was started by pulverizing moringa seeds then sieved with an 80 mesh sieve and heated at 105⁰C for 2 hours to reduce the water content. The process of aeration and coagulation was continued by varying the dose of coagulant 45; 55; 65; 75; 85 g and variation of stirring time 15; 30; 45; 60; 75; 85 minutes. Based on the research results, the best time and dose were 75 minutes and 75 g with a percentage of COD removal of 97.5%, turbidity 81%, TDS 32.45%, conductivity 27.01%, an optimum pH value of 4.2 was obtained. The FTIR characterization results obtained the highest peak of 2926.01 cm-1 indicating the presence of a carboxylic acid compound identifying the O-H functional group and experiencing a slight shift in the peak after coagulation and aeration of 2924.09 cm-1, there was no significant change in solid structure. From these results it can be concluded that moringa seed biocoagulant is able to reduce contaminants in tofu waste.